Systemic immune-inflammation index in twin pregnancies compared to singleton pregnancies - Ezgi Turgut; Bedri Sakcak; Deniz Oluklu; Şule Göncü Ayhan; Dilek Şahin (Perinatal Journal, 2021)
Objective To evaluate the systemic immune-inflammation index (SII) in twin pregnancies. Methods The retrospective study included 200 twin (dichorionic/ diamniotic and monochorionic/diamniotic) and 200 singleton pregnancies (control group). All pregnant women were in the first trimester (<14 weeks of gestation). The study and the control groups were compared in terms of demographic characteristics, laboratory test results, and SII values. Results The mean week of gestation was 9.7±2 in dichorionic diamniotic twin pregnancy group, 10.4±2 in monochorionic diamniotic twin pregnancy group and 9.4±2 for the control group (p=0.083). The lymphocyte value was lower in the dichorionic group and monochorionic group than in the control group (p=0.020 and p=0.020, respectively). The platelet-to-lymphocyte ratio (PLR) values were higher in the dichorionic group than in the control group (p=0.002). However, there was no statistical difference between the groups for neutrophil-to-lymphocyte ratio (NLR) and SII values (p>0.05). Conclusion Physiological inflammatory/immune reaction of early pregnancy may affect PLR values in twin pregnancies. We observed that chorionicity is considerable for these inflammatory indices, especially for dichorionic twin pregnancies. However, we could not detect a significant change in SII values in twin pregnancy.